PETA POTENSI KERUSAKAN BANGUNAN AKIBAT KERENTANAN GERAKAN TANAH DI DAERAH KALIREJO KULONPROGO YOGYAKARTA - Sari, Sely Novita; Prastowo, Rizqi (ReTII, 2019)
Pre-disaster mitigation should have become a culture in Indonesia to reduce the number of material casualties and fatalities. Landslides due to fractures are the main disasters in the Kalirejo area. Disaster management efforts are always carried out, namely by mitigating landslides, namely mapping, investigating, examining, monitoring, socializing, and examining landslides. Mapping buildings that are in disaster prone areas to be a pre-disaster mitigation that can be done, the purpose of this study is to map the potential damage to simple buildings due to the potential for land fractures in the Kalirejo area. The method used is to conduct a field survei by assessing existing buildings in the Kalirejo area and classifying them as safe, unsafe and insecure by giving red, yellow and green colors when mapping and plotting with a map of the potential of the Kalirejo area. The results obtained are a map of potential damage to buildings due to land fractures in the Kalirejo area and there is 1 red unsafe building located in a zone prone to high ground movements, 4 green safe buildings located in a high ground movement prone zone, 9 red unsafe buildings are located at the zone is prone to ground movement, 29 yellow unsafe buildings are located in the zone which is prone to ground movement, 47 the green building is located in zone which is prone to movement of land